The influence of personal factors on professional employees’ intention to stay: job satisfaction as mediator - Kusnin, Nurhazimah; Mohd Rasdi, Roziah (Human Resource Management Academic Research Society, 2018)
One of the most emerging issues in the field of Human Resource Development is how to effectively help professional employees to retain in organizations. Structural equation modelling (SEM-AMOS) was employed to examine factors influencing intention to stay among professionals and the mediation role of job satisfaction in the correlational relationships. Survey forms were collected from 457 professionals in Malaysia. The results revealed that personal-related factors (emotional intelligence and self-efficacy) have significant impact on professionals’ intention to stay, and job satisfaction mediated the relationship between personal-related factors and intention to stay. The findings of this study are useful for HRD practitioners to develop the interventions to assist individuals and organizations towards successful self-development and sustainable organizations.